2009
DOI: 10.1016/j.wasman.2008.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Municipal solid waste management in Malaysia: Practices and challenges

Abstract: Rapid economic development and population growth, inadequate infrastructure and expertise, and land scarcity make the management of municipal solid waste become one of Malaysia's most critical environmental issues. The study is aimed at evaluating the generation, characteristics, and management of solid waste in Malaysia based on published information. In general, the per capita generation rate is about 0.5-0.8 kg/person/day in which domestic waste is the primary source. Currently, solid waste is managed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
199
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(235 citation statements)
references
References 3 publications
6
199
0
6
Order By: Relevance
“…Manaf, Samah, and Zukki (2009) reported that domestic wastes is the primary source of the generation of solid wastes as a result the high concentration of Cd in Malaysia and its coast.…”
Section: Siltmentioning
confidence: 99%
“…Manaf, Samah, and Zukki (2009) reported that domestic wastes is the primary source of the generation of solid wastes as a result the high concentration of Cd in Malaysia and its coast.…”
Section: Siltmentioning
confidence: 99%
“…Based on Table 3 in comparison with Table 4, the combined data was formed into the Table 5 below whereby the data of food waste composition also included in which significant differences were seen between both methods [28]. The literature also stated that only 1% of C, H, S and O were based on mass balance calculation whereby 61% of data were obtained using direct chemical analysis [28].…”
Section: Comparison Between Ultimate Anaysis and Chns Analyzermentioning
confidence: 99%
“…The literature also stated that only 1% of C, H, S and O were based on mass balance calculation whereby 61% of data were obtained using direct chemical analysis [28].…”
Section: Comparison Between Ultimate Anaysis and Chns Analyzermentioning
confidence: 99%
“…Rapid economic development and population growth, inadequate infrastructure and land scarcity was Malaysia's most critical issues in managing the municipal waste. As stated by [2], the per capita generation rate of municipal waste is about 0.5 to 0.8 kg/person/day, which domestic waste is the primary sources. Agriculture waste, industrial waste, domestic waste and construction waste were wastes that are trying to be developed by researchers and commercialize as construction materials in replacing cement.…”
Section: Introductionmentioning
confidence: 99%